2005
DOI: 10.1055/s-2004-830517
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transduction Mediating Gene Expression of SP1, LHβ-Subunit and GH in Response to GnRH or GHRH in the Postnatal and Fetal Porcine Anterior Pituitary in Vitro

Abstract: To clarify signal transduction pathways mediating putative gene expression of transcription factor SP1 (selective promoter factor 1 or specificity protein 1) by GnRH or GHRH porcine anterior pituitary monolayer cultures were exposed for various time periods to GnRH, GHRH, activators of adenylate cyclase (AC) or proteinkinase C (PKC), and mRNA levels of SP1, LHbeta-subunit, and GH were determined by multiplex RT-PCR. In many experiments LH and GH release were measured as well for comparison. Another approach wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…All photographs were taken with a 1009 lens on an Olympus IX70 microscope LH\beta[ gene transcription increased with acute activation (6 h) of the GnRH receptor or PKC, but not calcium influx, in a promoter activity assay. Blocking PKC induction prevented the acute action of the GnRH and unmasked the acute repression of LH\beta[ transcription by calcium (Vasilyev et al 2002;Zeng et al 2005). Of interest is the fact that others and ourselves have observed significantly different activities of the LH\beta[ promoter after treatment with various calcium-affecting drugs, and our results showed that EGTA inhibits zebrafish LH\beta[ promoter activity, but others found that it did not affect the promoter (Call and Wolfe 1999).…”
Section: Discussionmentioning
confidence: 53%
“…All photographs were taken with a 1009 lens on an Olympus IX70 microscope LH\beta[ gene transcription increased with acute activation (6 h) of the GnRH receptor or PKC, but not calcium influx, in a promoter activity assay. Blocking PKC induction prevented the acute action of the GnRH and unmasked the acute repression of LH\beta[ transcription by calcium (Vasilyev et al 2002;Zeng et al 2005). Of interest is the fact that others and ourselves have observed significantly different activities of the LH\beta[ promoter after treatment with various calcium-affecting drugs, and our results showed that EGTA inhibits zebrafish LH\beta[ promoter activity, but others found that it did not affect the promoter (Call and Wolfe 1999).…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, TATA binding protein ( TBP ), general transcription factor IIH subunit 2 ( GTF2H2 ), and general transcription factor IIB ( GTF2B ) as general transcription factors, assemble on the promoters of the gene transcribed by RNA polymerase II, which trigger transcriptional regulation by interacting with gene regulatory factors ( Sperling, 2007 ; Bieniossek et al, 2013 ). In general, TBP interacts with TBP-associated factors ( TAFs ) to identify and activate gene transcription, of which selective promoter factor 1 ( SP-1 ), as one of the TAFs, could induce GnRH responsiveness to the LHβ promoter by mediating the actions of both adenylate cyclase (AC) and protein kinase C (PKC) ( Zeng et al, 2005 ). Moreover, TAF9 and GTF2H2 have been shown to play roles in the estrogen signaling pathway ( Markaverich et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the human SP22 promoter was activated by Sp1 (34). In tum, Spl has been implicated in the GnRH-induced stimulation of the LHp gene promoter (35,36). SP22 has been linked to nuclear AR function.…”
Section: Discussionmentioning
confidence: 99%